The Effect of Liquidity and Profitability on Stock Prices With Dividend Policy as Moderation in Manufacturing Companies Listed on the Stock Exchange in 2016-2018: Pengaruh Likuiditas Dan Profitabilitas Terhadap Harga Saham Dengan Kebijakan Dividen Sebagai Moderasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Pada Tahun 2016-2018 - Mardianti, Any; Dewi, Santi Rahma (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of liquidity, and profitability on stock prices with dividend policy as a moderating variable on the Indonesia Stock Exchange in 2016 – 2018. The method used is purposive sampling and produces 38 sample companies, so the total research data is 114 data. Hypothesis testing is done by using multiple linear regression analysis and regression analysis. The results show that liquidity has a significant positive effect on stock prices, profitability has a significant positive effect on stock prices, dividend policy has a significant positive effect on stock prices. Dividend policy weakens the relationship between liquidity and firm value. Dividend policy strengthens the relationship between profitability and firm value. The results of the coefficient of determination test show that the independent variable, moderating variable and the interaction of the two variables are only able to explain the dependent variable by 22.9%, while the remaining 78.1% is explained by other variables not explained in this study.